2012
DOI: 10.1039/c2an35908a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ascorbic acid and folic acid based on water-soluble CuInS2 quantum dots

Abstract: In this paper, water-soluble CuInS(2) ternary quantum dots (QDs) modified by mercaptopropionic acid (MPA) were directly synthesized by hydrothermal method. Ascorbic acid (AA) can induce the fluorescence enhancement of MPA-capped CuInS(2) QDs and can be used for the detection of AA. Under the optimized conditions, the relationship between the fluorescence intensity of the CuInS(2) QDs and AA concentration was linear in the range of 0.25-200 μmol L(-1). Most relevant molecules and physiological ions had no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…In this connection, many mechanisms have been proposed for the design of sensors for various analytes, such as inorganic ions [37,38,[53][54][55][56][57], biomolecules [22,30,33] and active pharmaceutical ingredients [34,35] based on the surface states fluorescence modulation of QDs. Similarly, herein we have suggested that same approach can also be utilized for turn-on sensing of d-PA based on MPA-CdS QDs.…”
Section: Possible Sensing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, many mechanisms have been proposed for the design of sensors for various analytes, such as inorganic ions [37,38,[53][54][55][56][57], biomolecules [22,30,33] and active pharmaceutical ingredients [34,35] based on the surface states fluorescence modulation of QDs. Similarly, herein we have suggested that same approach can also be utilized for turn-on sensing of d-PA based on MPA-CdS QDs.…”
Section: Possible Sensing Mechanismmentioning
confidence: 99%
“…Recently, the studies on detecting and identifying biomolecules with QDs such as CdS, CdSe, CdTe, CuInS 2 etc. as optical sensors have attracted considerable attention [22][23][24][25][26][27][28][29]. Wang et al [30] has reported the fluorescent probe for cystein based on citrate (Cit)-capped CdS quantum dots (QDs) and it offers good sensitivity and selectivity for detecting cystein.…”
Section: Introductionmentioning
confidence: 99%
“…FA with different concentrations were introduced into the diluted plasma samples to prepare the spiked samples. 27,28 Human blood serum samples were obtained from Medical College of Beihua University, China, and all analyses were performed at the Nanotechnology & Application Laboratory. All experiments were performed in compliance with the relevant laws and national guidelines (Ethical Guidelines for Biomedical Research on Human Participants, provided by China National Health and Family Planning commission), and the ethical clearance for the same was provided by the Medical College of Beihua University, Jilin City.…”
Section: Real Sample Testmentioning
confidence: 99%
“…Electrochemistry 0-5000 0.61 [43] Electrospraying method 0-1000 7.35 [44] Fluorescence quenching 8-10 2.4 [45] Ratiometrically fluorescent 3-40 1.5 [46] Fluorescence enhancement 250-200 50 [47] Fluorescence turn on 2-100 0.17 [48] Colorimetry 0.1-2.5 0.049 [14] Colorimetric sensor 0.25-20 0.062 This method investigated using the same experimental conditions. As shown in Fig.…”
Section: Selectivity For Aa Detectionmentioning
confidence: 99%